The Pengembangan Ensiklopedia Terintegrasi STEM (Science, Technology, Engineering, Mathematics) Sebagai Pengayaan Bagi Peserta Didik Di Sekolah Dasar: Pengembangan Ensiklopedia Terintegrasi STEM (Science, Technology, Engineering, Mathematics) Sebagai Pengayaan Bagi Peserta Didik Di Sekolah Dasar - Vera Yuli Erviana (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2019)
This study aims to develop an integrated thematic learning encyclopedia media STEM that can help increase understanding of the material and improve critical and creative thinking skills in students. This type of research is Research and Development (RnD) using ADDIE research design. The experimental subjects used in this study were grade 3 students of Muhammadiyah Ambarbinangun Elementary School, totaling 49 children. Data collection techniques are interviews, questionnaires, and tests. Data collection instruments are encyclopedia assessment sheets, test results, and interviews. Data analysis techniques are qualitative and quantitative data. The results showed that the average of expert validation test assessments were 86.35 with